Impact of El Niño phenomenon, Southern Oscillation (ENSO) on hydrometeorology variability at Valle del Cauca State, Colombia, using canonical correlation analysis - Carvajal, Yesid, author; Marco, Juan B., author; Colorado State University, publisher (Colorado State University. Libraries, 2007)
The linear teleconnections between the ENSO phenomenon and Valle del Cauca State, Colombia (Colombia) monthly inter annual and seasonal hydro meteorological, were studied. Two multivariate statistical techniques were used: Empirical orthogonal functions (EOFS) and the canonical correlation analysis (CCA). The ENSO effect is higher on flows that on precipitation. It was concluded that in March-April-May (MAM) and September-October-November (SON) periods the ENSO association and effect on regional hydrometeorology is lower; while, in December-January-February DJF and June-July-August (JJA), the effect is higher. The inclusion of principal components of macroclimatic variables such as variables predictors for the precipitation and flows models improved the prediction, indicating that they contribute with additional information. The flow models showed good fit and they can be used for prediction. Likewise, the multivariate EOFS and CCA methods proved to be valuable tools in the study of climate variability so as to understand the relationships between ENSO phenomenon with the region hydro meteorological regime.
Hydrology days 2007
AGU hydrology days 2007
2007 annual AGU hydrology days was held at Colorado State University on March 19 - March 21, 2007.